Measuring Nation States' Deliberativeness: Systematic Challenges, Methodological Pitfalls, and Strategies for Upscaling the Measurement of Deliberation - Dannica Fleuß; Karoline Helbig (Political Studies, 2021)
A theoretically reflected and empirically valid measurement of nation states' democratic quality must include an assessment of polities' deliberativeness. This article examines the assessment of deliberativeness suggested by two sophisticated contemporary measurements of democratic quality, that is, the Democracy Barometer and the Varieties of Democracy-project. We feature two sets of challenges, each measurement of deliberativeness must meet: First, it must address the methodological challenges arising in the course of conceptualizing, operationalizing, and aggregating complex concepts (see Munck and Verkuilen, 2002). Second, attempts to measure nation states' deliberativeness are confronted with specific conceptual and systematic challenges which we derive from recent deliberative democracy scholarship. We argue that both Democracy Barometer and Varieties of Democracy-project provide highly sophisticated assessments of democratic quality, but ultimately fail to capture nation states “deliberativeness” in a theoretically reflected and methodologically sound manner. We examine the methodological, pragmatic, and systematic reasons for these shortcomings. The crucial task for measurements of nation states' deliberativeness consists in providing a conceptual approach and methodological framework for “upscaling” existing meso-level measurements (such as the DQI). The concluding section presents conceptual and methodological strategies that can enable researchers to meet these challenges and to provide a theoretically grounded and empirically valid measurement of nation states' deliberativeness.
Keywords: 300; deliberative democracy; deliberation; measurement of democracy; measurement of democratic quality; deliberative systems; upscaling deliberation